A good bot roast. (Economist, 2007)
The article reports on a new investigation by the U.S. Federal Bureau of Investigation (FBI) designed to combat 'bot-nets,' networks strung together with hijacked computers used to steal data and send spam, causing disruptions in the Internet. The article reports that the FBI sees these bot-nets as a threat to national security, and that solving the problem of them is difficult because most people whose computers have been hacked into don't know it.